The evidence-based practice ideologies - Mantzoukas, Stefanos (Nursing philosophy, 2007)
This paper puts forward the argument that there are various, competing, and antithetical evidence-based practice (EBP) definitions and acknowledges that the different EBP definitions are based on different epistemological perspectives. However, this is not enough to understand the way in which nurse professionals choose between the various EBP formations and consequently facilitate them in choosing the most appropriate for their needs. Therefore, the current article goes beyond and behind the various EBP epistemologies to identify how individuals choose an epistemology, which consequently will assist our understanding as to how an individual chooses a specific EBP formation. Individuals choose an epistemology on the mere belief that the specific epistemology offers the ideals or ideas of best explaining or interpreting daily reality. These ideals or ideas are termed by science, history, and politics as ideology. Similarly, individual practitioners choose or should choose between the different EBP formations based on their own personal ideology. Consequently, this article proceeds to analyse the various ideologies behind different EBP definitions as to conclude that there are two broad ideologies that inform the various EBP formations, namely the ideology of truth and the ideology of individual emancipation. These two ideologies are analysed and their connections to the various EBP formations are depicted. Eventually, the article concludes that the in-depth, critical, and intentional analysis by individual nurses of their own ideology will allow them to choose the EBP formation that is most appropriate and fitting for them, and their specific situation. Hence, the conscious analysis of individual ideology becomes the criterion for choosing between competing EBP formations and allows for best evidence to be implemented in practice. Therefore, the best way to teach EBP courses is by facilitating students to analyse their own ideology.